International competitiveness : is the reduction of wages a solution? An evaluation of the Portuguese case - Vaz, Elsa Cristina (2013)
The purpose of this paper is to analyse, for the case of Portugal, the effectiveness of wage reduction ‐ a current proposal since 2011 to help the country to reverse the high public and external debt - in promoting the efficiency and international competitiveness of the economy. A static multi‐sector and single‐country general equilibrium model is used and data is collected from the GTAP7 Database. The model allows the measurement of changes by sector. The simulations performed show that extending the reduction of wages already deployed by the government in the public sector to the private sector leads to a positive impact on employment (both skilled and unskilled labour), production and volume of exports in all sectors except those that are R&D intensive, the latter having a low weight in the Portuguese economy. However, it is possible that the positive results in terms of external competitiveness are not sustainable, as the impact on productivity is negative, albeit small, for most sectors. There are also reasons for concern regarding the observed deterioration of the trade balance of most sectors, the exception being the traditional labour intensive sectors, which show good prospects in this respect.